SYSTEM FOR THE DETERMINATION OF THERMAL CONDUCTIVITY OF SOLIDS BETWEEN 65 K AND 300 K - MAYER, ER; CASTILLO, LM DEL; CAREAGA, JA (UNAM, Ctr Invest Mat, 1978)
A cryogenic system for the determination of thermal conductivity of solids between 65 degrees K and 300 degrees K is described, in which the standard technique of establishing a temperature gradient on the specimen by dissipating on it a known quantity of
THE AUK
Keywords: SYSTEM, DETERMINATION, THERMAL, CONDUCTIVITY, SOLIDS; FISICA; FISICA DEL ESTADO SOLIDO; PROPIEDADES TERMICAS DE LOS SOLIDOS